Providing a model of the quality of working life with a strategic approach of human resources in the administrative system - Vahid Mohammadi; Musa Rezvani Chaman Zamin; Badri Abbasi; Morteza Hazraty; Mehran Nasirzad (مدیریت و چشم انداز آموزش)
Abstract The purpose of this research is to provide a model of the quality of working life with a strategic approach of human resources in the administrative system of Bank Mellat. The research method is applicable in terms of purpose, mixed (qualitative-quantitative) in terms of implementation, and descriptive-survey in terms of nature and method. The statistical population included 20 academic and banking experts in the qualitative section, and 378 employees and experts of Mellat Bank across the country, who were selected as a sample in the quantitative section, and simple stratified sampling was used. Data collection was done by semi-structured interviews in the qualitative part, and by questionnaire in the quantitative part. MAXQDA coding and software were used in qualitative part data analysis, and SPSS and AMOS software were used in quantitative part. The results of the t-test showed that all 5 main components, 20 sub-components, and 118 sub-components identified have an impact on the quality of work life with the strategic approach of human resources in the administrative system of Bank Mellat. The results obtained from the model fit indices also showed that the research model is a good model in terms of fit with the experimental data. The results of the t test in this evaluation showed that the most effective component on the pattern of quality of working life with a strategic approach to human resources in the administrative system of Bank Mellat is the component "Working relationships between colleagues" with a statistical value (t = 31.045), and the least effective component is also the component "decision support systems in managers' decision-making" with a statistical value (t = 13.102). Extended abstract Introduction Human resources is considered as one of the most basic strategies of any organization. Undoubtedly, the success of organizations and work environments depends on the efficient use of human resources based on behavioral science (Rasouli et al, 2022). In organizations, due to the existence of human forces, each of which has its own behavioral and personality complexities, the work of human resource management and organizational behavior management is crucial and somewhat difficult. Also, due to the small issues that exist in the social life of people both in the organization and in the family, obstacles and challenges may arise that reduce the productivity and motivation of the organization's employees and prevent the organization to reach its goals, or at least will cause a delay in achieving those goals and also prevent employees from enjoying their work life or even their personal life (Kotobi et al, 2021). Undoubtedly, work is not just a tool or a simple means of making a living; it is a multi-factor process in which employees are the center of gravity and its driving force (Shabani Beshli, 2021). The socially responsible behavior of organizations, which also affects their economic income, is to provide a safe and high-quality work environment for employees (Ebrahimbay Salami et al, 2022). The quality of work life can be considered an integral part of the overall quality of life (Jin & Lee, 2021). The quality of working life is an important approach in maintaining human values, which has been neglected due to the great attention to technological progress and economic growth (Mousazadeh et al, 2021). Theoretical Framework Quality of working life Ahmad (2013) defines the quality of working life "as a goal and a process". The goal is to create more effective and satisfying jobs and environments for people at all levels of the organization, and the process of realizing this goal is active participation. The term "quality of working life" means differently for different people. Some refer to it as a welfare program, while others, especially employees, refer to it as a subtle incentive for employees or simply another productivity tool (Abebe & Assemie, 2023. Quality of working life with a strategic approach Strategic human resource development can be considered as a proactive and system-wide intervention that is linked to strategic planning and culture change. In the traditional view, education and development were viewed as reactive and partial interventions in response to specific issues. Human resource development will be strategic only when it is linked with the overall strategy of the organization. Strategic management allows the organization to act in a creative and unique way and not to act passively to shape its future. This management style makes the organization take initiative and control the future. The strategic development of human resources deals with issues such as creating a dynamic organization and providing training and learning opportunities for employees in order to improve organizational, group and individual performance (Mataji Nimuri & Niazian, 2021. Abebe & Assemie (2023) investigated the quality of working life and organizational commitment of employees in Ethiopian universities. The results showed that service compensation, reward, and balance between work and life were statistically significant and positively related to the organizational commitment of university employees. In addition, the quality of work life has a statistically significant and positive relationship with the organizational commitment of higher education teachers. Akinwale et al., (2023) investigated the path of brain drain and quality of work life among university professors in Nigeria: Uninterrupted University Union (ASUU) strike. The results showed that there is poor service status among Nigerian lecturers, compensation system is poor, funding of academic research is poor, and lack of autonomy is troublsome for the quality of working life experienced in Nigerian tertiary institutions today. Research methodology The research method is applicable in terms of purpose, mixed (qualitative-quantitative) in terms of implementation, and descriptive-survey in terms of nature and method. The statistical population included 20 academic and banking experts in the qualitative section, and 378 employees and experts of Mellat Bank across the country, who were selected as a sample in the quantitative section, and simple stratified sampling was used. Data collection was done by semi-structured interviews in the qualitative part, and by questionnaire in the quantitative part. Research findings MAXQDA coding and software were used in qualitative part data analysis, and SPSS and AMOS software were used in quantitative part. The results of the t-test showed that all 5 main components, 20 sub-components, and 118 sub-components identified have an impact on the quality of work life with the strategic approach of human resources in the administrative system of Bank Mellat. The results obtained from the model fit indices also showed that the research model is a good model in terms of fit with the experimental data. The results of the t test in this evaluation showed that the most effective component on the pattern of quality of working life with a strategic approach to human resources in the administrative system of Bank Mellat is the component "Working relationships between colleagues" with a statistical value (t = 31.045), and the least effective component is also the component "decision support systems in managers' decision-making" with a statistical value (t = 13.102). Conclusion The present study was conducted with the aim of providing a model of the quality of working life with a strategic approach of human resources in the administrative system of Bank Mellat. The results of this research are aligned with the results of Abebe & Assemie (2023), Akinwale et al., (2023), Di et al, (2023), Akter et al, (2023), Ashourzadeh et al, (2022), Algazlan et al, (2022), Eliyana & Anwar (2022), Rasouli et al, (2022), Ebrahimbay Salami et al, (2022), Safari & Ghasemian Asl (2022), Negahdari & Anuri (2022), Golshahi & Jafarpor Hamedani (2022), Heydarifard et al, (2022), Ramezannia et al, (2021), Latifi & Khalili (2021), Rahnama et al, (2021), Diana et al, (2022), Arief et al, (2021), Asadi Khanouki & Hajizadeh (2021), Mousazadeh et al, (2021), and Abrahams et al, (2021). Abebe & Assemie (2023) showed that service compensation, reward, and balance between work and life were statistically significant and positively related to the organizational commitment of university employees. In addition, the quality of working life has a statistically significant and positive relationship with the organizational commitment of higher education teachers. According to the results of this research, the following suggestions are presented: